The Elements Determining the Contemporary State of Affairs of the Sea Food Harvesting Community along the Coastal Belt of Mullaitivu District - Umashankar, K.; Shalton, A.R. (Faculty of Agriculture University of Jaffna, Sri Lanka, 2017)
Mullativu is one of the districts located along the Northern coastal belt of Sri Lanka, relatively more viable for the fishing industry. The pre-civil unrest time, was quite prosperous for the people of Mullativu. The thirty years of civil commotion dismantled and destroyed the social structure and the infrastructure. Presently as the people return to their ancestral land they are faced with a hostile climate and non-climatic factors such as the use of illegal fishing equipment, poaching, over harvesting, etc. A radical change in the life style of rural folk whose living was more in keeping with nature, could be another cause for their regression. The net result being that they do not harvest a return proportionate to the time, labour and the capital invested. Thus, these people are caught up in a whirl pool of poverty from which they are unable to emerge. Hence this research attempted to find out the socio-economic elements determining the contemporary state of affairs of the sea food harvesting community of the Mullaitivu District. A total of 192 fishing households were selected using purposive random sampling method, during the period of February/2017 to April/2017. The poverty level of the respondents was assessed based on the Multidimensional Poverty Index in compliance with UNDP HDRO standards. Using the Binary Response Logistic Model, an effort was made to decipher what community base or socio-economic characters It was found that membership in were responsible for their state of poverty. fishermen organization (-0.0175) and income generated from fishing activity (-0.226), and income diversification practices of heads of household's (-0.0953) influence poverty negatively at 1%, 5% and 5% significant level respectively, whereas, social interaction activity (+2.857) contributed positively towards poverty at 1% significant level. It is recommended by the researcher that the activity which influence poverty positively be discouraged and negatively be encouraged and fostered. Income should be enhanced through furthering the activity in the sea gathering a better harvest. This harvest should be sustained through proper management practices. Better marketing facilities and value addition services for fish product in this study area be provided. Encouraging the fishermen to join suitable fishermen's organization, which would provide them advantages in 52 enhancing their bargaining power, increased access to capital, technology and market information, would certainly result in poverty reduction considerably. Further the researchers recommend skill training to all fishermen that may help them a long way to employ themselves profitably. Finally, social activity involving people here and abroad and functions held at home and an artificial prosperity seen to take away financial resources which could be easily utilized for investment in fishing. All of these can be accomplished by implementing a tailormade community specific extension program
Keywords: Fisheries; Poverty; Logistic model; Extension program; Mullaitivu district